Los Departamentos de Orientación en los IES : Estudio de las disociaciones entre percepciones reales y normativa legal - Rufino Cano González (Universidad de La Rioja, 2013)
The fact that we're just to celebrate the first ten years of the LOGSE implementation, is reason enough to reflect, from the theory, and evaluate, from the practice, the mutual responsibility in one of the major levels of the organisational structure of the IES (Institutes of Secondary Education), that is the case of the Orientation Department. Our aim is, then, to evaluate this relationship, theory-practice, through a comparative analysis between the prescriptive legal normative from the Public Administration and what has been described in the different experiences in Orientation developed in the institutes of Secondary Education in Valladolid and its province, with the ultimate intention of formulating proposals and improvement recommendations basalt on the results of our research.